Human Resource practices in RMG industry. An experience with Maruhisa Pacific Co. Ltd. - Rahman, Atia (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2019.